Tomatidine Attenuates Airway Hyperresponsiveness and Inflammation by Suppressing Th2 Cytokines in a Mouse Model of Asthma - Chieh-Ying Kuo; Wen-Chung Huang; Chian-Jiun Liou; Li-Chen Chen; Jiann-Jong Shen; Ming-Ling Kuo (Hindawi Limited, 2017)
Tomatidine is isolated from the fruits of tomato plants and found to have anti-inflammatory effects in macrophages. In the present study, we investigated whether tomatidine suppresses airway hyperresponsiveness (AHR) and eosinophil infiltration in asthmatic mice. BALB/c mice were sensitized with ovalbumin and treated with tomatidine by intraperitoneal injection. Airway resistance was measured by intubation analysis as an indication of airway responsiveness, and histological studies were performed to evaluate eosinophil infiltration in lung tissue. Tomatidine reduced AHR and decreased eosinophil infiltration in the lungs of asthmatic mice. Tomatidine suppressed Th2 cytokine production in bronchoalveolar lavage fluid. Tomatidine also blocked the expression of inflammatory and Th2 cytokine genes in lung tissue. In vitro, tomatidine inhibited proinflammatory cytokines and CCL11 production in inflammatory BEAS-2B bronchial epithelial cells. These results indicate that tomatidine contributes to the amelioration of AHR and eosinophil infiltration by blocking the inflammatory response and Th2 cell activity in asthmatic mice.